2021
DOI: 10.1111/jfpe.13687
|View full text |Cite
|
Sign up to set email alerts
|

Agglomerated mushroom (Agaricus bisporus) powder: Optimization of top spray fluidized bed agglomeration conditions

Abstract: Agglomeration process improves instant properties of powders and increases consumer appreciation, reduces losses during production, and facilitates the processability of these powders in the industry. Mushroom powders (MP) have been subjectedto agglomeration process at different process parameters: inlet air temperature (50-80 C), atomizing pressure (0.5-1.5 bars), and sprayed pure water amount (20-50 g) and the effects of process parameters on the physical and morphological properties of MP were investigated.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…Turchiuli et al [16] also stated that bed hydrodynamics decreased with time due to particle enlargement as the agglomeration progressed. Our findings were consistent with those reported for many raw materials, such as rice protein concentrate [2], pea protein isolate [11,12], plant protein powder [13], and mushroom powder [18].…”
Section: Solid Occupancy Without Bed Height Controlsupporting
confidence: 92%
See 1 more Smart Citation
“…Turchiuli et al [16] also stated that bed hydrodynamics decreased with time due to particle enlargement as the agglomeration progressed. Our findings were consistent with those reported for many raw materials, such as rice protein concentrate [2], pea protein isolate [11,12], plant protein powder [13], and mushroom powder [18].…”
Section: Solid Occupancy Without Bed Height Controlsupporting
confidence: 92%
“…The agglomerated particles (as seen in Figure 8c-f) exhibited a larger and looser structure, characterized by irregular shape, with a porous surface that facilitated water absorption during reconstitution. Increases in irregularity and porosity of the agglomerates were previously reported [2,11,12,[18][19][20]. Bed stability control is infrequently utilized in fluidized-bed agglomeration processes.…”
Section: Particle Morphology (Sem)mentioning
confidence: 76%
“…The literature does not report investigations in berry-type fruits in agglomerated food products. The work carried out by Atalar et al [ 41 ] in agglomerated powder of commercial yoghurts, who reported S values of 55% and a decrease in We for the load material (2 h → 7–8 s); in addition, by Atalar et al [ 42 ], who reported for the agglomerated powder of the fungus ( Agaricus bisporus ): a decrease in We from values > 1 h → 3.75–22.5 s and an increase in S 21 0.6 → 27.6%).…”
Section: Resultsmentioning
confidence: 99%
“…C moisten a more significant number of fine particles of ABPM, increasing the liquid bridges, the size of the agglomerate and the cohesion forces, acting the system with a protective effect of Vit. C and the present active components [ 42 , 44 ]. Finally, the response volume plot summarizes the most favourable Vit.…”
Section: Resultsmentioning
confidence: 99%
“…Porosity ( Ɛ ) was calculated using the following formula (Equation 1), utilizing the relationship between tapped bulk density ( ρT ) and particle density ( ρP ) (Ji et al, 2015). Ɛ=()italicρPgoodbreak−italicρTitalicρPx100 To determine the wettability properties of the powder, 5 g of spray‐dried boza powder was weighed and the time required for them to completely disappear from the surface in 100 ml of distilled water through a calibrated funnel (with a measuring width of 50 mm) was measured (Atalar et al, 2021). For solubility analysis, 0.1 g of boza powder was dispersed in 24.9 g of distilled water, mixed in a water bath at 25°C, and the mixture was centrifuged at 2500g for 20 min, and then 10 g of supernatant was dried in an oven at 105°C until it reached a constant weight.…”
Section: Methodsmentioning
confidence: 99%